Pemberian Ketebalan Tanah Mineral pada Lahan Gambut untuk Memperbaiki Pertumbuhan Beberapa Varietas Padi Gogo (Oriza Sativa L.) - Maslaita Maslaita (JURNAL AGROPLASMA, 2022)
Provision of Mineral Soil Thickness in Peatlands to Improve Growth and Varieties of Upland Rice (Oriza Sativa L.) This study aims to improve and is expected to be useful for increasing the growth of upland rice varieties with the right thickness of mineral soil on peatlands. This research was conducted on the land of the Technical Implementation Unit of the Agricultural Extension Center Agency (UPTB BPP), Ujung Bawang Village, Singkil District, Aceh Singkil Regency, from April to July 2020. The study used a Randomized Block Design (RAK) with 2 (two) factors and 4 (four) repetitions. The first factor is variety (V) with 4 (four) levels, namely the Local Siliam variety, Situ Bagendit variety, Situ Patenggang variety, and Batutengi variety. The second factor is the thickness of mineral soil applied on peat soil with 5 (five) levels, namely without mineral soil/0 cm as control (100% peat), 5 cm, 10 cm, 15 cm, 20 cm. The results of this study showed that the treatment of upland rice varieties showed a significant effect on growth and production variables such as plant height 4, 6, 8 and 10 weeks after planting (MST), the number of tillers at 4, 6, 8 and 10 WAP, the number of productive tillers.Keywords: Soil Thickness, Peat, Rice Varieties, Singkil